Material Suitability Testing for Nonmedical Grade Community Face Masks to Decrease Viral Transmission During a Pandemic. (27th October 2021) - Varallyay, Csanad; Li, Ningcheng (Peter); Case, Brendan; Wolf, Bryan
Abstract: Objectives: Cloth face covering has been recommended by the Centers for Disease Control and Prevention to decrease community viral transmission. This study aims to determine the filtration efficiency and airflow resistance of common household materials available for homemade mask production by comparing numbers of fabrics, various layers, and manipulation. Methods: Common household woven, knitted, and nonwoven fabrics were tested for filtration efficiency using a fit testing setup and airflow resistance with pressure gauge setup. Three different levels of layering (1, 2, and 4) were tested. Some fabric material was further tested after washing and drying. Filtration performance, the area under the fitted curve comparing airflow resistance and filtration efficiency, was calculated for each fabric material and compared. Results: Layering increased filtration efficiency and airflow resistance ( P < 0.0001 and P < 0.01, respectively). Polyester felt demonstrated the highest filtration performance index ( P < 0.0001), higher than all tested 100% cotton materials (all P < 0.05) as well as surgical masks ( P < 0.05). Washing plus drying did not alter filtration performance significantly ( P > 0.05). Conclusions: A filtration performance of common household fabrics were compared. Homemade mask designers and producers will have improved data to better balance effectiveness, availability, and comfort with the goal of decreasing community viral transmission.